2014
DOI: 10.1111/anae.12604
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transthoracic echocardiographic data in major vascular surgery from a prospective randomised trial comparing sevoflurane and fentanyl with propofol and remifentanil anaesthesia

Abstract: SummaryThe aim of this study was to define pre-operative echocardiographic data and explore if postoperative indices of cardiac function after open abdominal aortic surgery were affected by the anaesthetic regimen. We hypothesised that volatile anaesthesia would improve indices of cardiac function compared with total intravenous anaesthesia. Transthoracic echocardiography was performed pre-operatively in 78 patients randomly assigned to volatile anaesthesia and 76 to total intravenous anaesthesia, and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Even if sevoflurane offered cellular protection via different mechanisms, such as intracellular signaling pathways [ 30 ] , mitochondrial function [ 31 ] , and potassium channels [ 32 ] , recent studies have suggested that sevoflurane does not significantly reduce mortality or major postoperative complications, such as myocardial infarction, ventilation time and intensive care unit stay [ 7 8 ] . The myocardial compensatory ability is significantly decreased in patients undergoing CABG, which might explain our finding that sevoflurane improved LV GLS, SV, and CO in patients with CAD, whereas Lindholm et al [ 33 ] found no significant echocardiographic differences between sevoflurane and TIVA in abdominal aortic surgery.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Even if sevoflurane offered cellular protection via different mechanisms, such as intracellular signaling pathways [ 30 ] , mitochondrial function [ 31 ] , and potassium channels [ 32 ] , recent studies have suggested that sevoflurane does not significantly reduce mortality or major postoperative complications, such as myocardial infarction, ventilation time and intensive care unit stay [ 7 8 ] . The myocardial compensatory ability is significantly decreased in patients undergoing CABG, which might explain our finding that sevoflurane improved LV GLS, SV, and CO in patients with CAD, whereas Lindholm et al [ 33 ] found no significant echocardiographic differences between sevoflurane and TIVA in abdominal aortic surgery.…”
Section: Resultsmentioning
confidence: 52%
“…In the present study, postoperative complications and cTnT discharge did not show notable differences; however, the cTnT levels decreased more quickly on postoperative day 1 and day 2. Consistent with these results, the recent mortality in cardiac surgery (MYRIAD) trial suggested that volatile agents might reduce postoperative myocardial injury in CABG patients [ 33 ] . The present results also showed that sevoflurane enhanced blood flow but reduced RI in the LIMA-LAD graft.…”
Section: Resultsmentioning
confidence: 65%
“…Chance corrected inter-observer agreement for trial eligibility was excellent (kappa = 0.82). Twenty-four trials were subsequently excluded for the following reasons: Not randomized (2), 5,6 pilot trial (4), 7-10 cross-over trial (2), 11,12 factorial (2), 13,14 multiple outcomes (5), [15][16][17][18][19] secondary analysis (4), [20][21][22][23] using dynamic sample size calculations (1), 24 non-inferiority trial (2), 25,26 and trial stopped early (2). 27,28 Trial selection process is shown in 0 1, sample-size calculation details of the 28 included trials are reported in Table 1, and a comparison of expected and actual treatment effects are provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Pre‐ and post‐operative echocardiographic examinations were performed in 154 patients . Compared to pre‐operative findings, significant increases in left ventricular end‐diastolic volume, left ventricular ejection fraction, left atrial max volume, cardiac output, E and É were observed post‐operatively (for all: P < 0.001).…”
Section: Resultsmentioning
confidence: 99%